Genetic variability for micronutrients under an aerobic condition in local landraces of rice from different agro-ecological regions of Karnataka, India (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Thuy NP, Nhu TTT, Trai NN, Nhu NK, Thao NHX, Phong VT, Khoa BD, Luan NT. 2023. Genetic variability for micronutrients under an aerobic condition in local landraces of rice from different agroecologicalregions of Karnataka, India. Biodiversitas 24: 1-10.Genetic variability is a fundamental reference for the innovative development of breeding programs to improve varieties and desirable traits. This study aimed to assess genetic variability for micronutrients (iron and zinc) and protein content under an aerobic condition in local landraces of rice (Oryza sativa L.) from different agroecological regions of Karnataka, India. Fifty-fivelocal landraces of ricefrom India were studied.High phenotypic and genotypic coefficient of variation was observed for grain yield per plant and moderate for the remaining traits. Heritability was high for most of the traits observed while moderatefor harvest index and grain yield plant-1. The genetic advance (GA) was high for the majority of yield and its attributing traits. GA as mean was high for grain yield per plant. Based on D2value, 50 genotypes were grouped into 8 clusters. Clusters VI and VIII are the largest and had accessions with the highest protein and zinc content. Marabatta, Jeerige Batta, Neerguli, Mugadh Sughanda, and Kesarnellu genotypes contained high grain protein and zinc content, whereas Naga Batta genotype has high iron content. Among the superior nutrient landraces, Neerguli, Jeerige Batta, DBN, Kesarnellu, and Doddiga genotypes had high grain yield plant-1.